1) on pose [tex]C= \frac{1+ \sqrt{5} }{2} [/tex] le nombre d'or
donc [tex]C^2=( \frac{1+ \sqrt{5} }{2} )^2= \frac{1+2 \sqrt{5}+5 }{4}= \frac{3}{2} + \frac{ \sqrt{5} }{2} [/tex]
aussi [tex]C+1= \frac{1+ \sqrt{5} }{2}+1= \frac{3}{2} + \frac{ \sqrt{5} }{2} [/tex]
donc on obtient : C²=C+1
2) de même [tex]C-1= \frac{1+ \sqrt{5} }{2}-1= \frac{-1}{2}+ \frac{ \sqrt{5} }{2} [/tex]
et [tex] \frac{1}{C}= \frac{2}{1+ \sqrt{5} }= \frac{2(1- \sqrt{5}) }{1^2- \sqrt{5}^2 }= \frac{-1}{2}+ \frac{ \sqrt{5} }{2} [/tex]
donc on obtient : C-1=1/C